MY SAY: Consider the Islamic financial option - Abd Razak, Dzulkifli (2008)
The global economic system continues to be plagued by a loss of confidence as markets worldwide plunge further, some hitting their lowest level in recent times. Meanwhile, the risk of deflation and recession is becoming real again. Japan's recessionhit economy is reportedly worsening, as is the US economy. These, predictably, will be followed by others in the coming months if nothing concrete happens soon. All this is too ironic as it was only in midSeptember that the then Republican presidential candidate, John McCain, announced: "The fundamentals of the economy are strong." Hours later, Lehman Brothers filed for bankruptcy — the largest in US history — and the Dow dropped 500 points, which only goes to show how volatile the situation is.